Family structure and children's educational attainment in transition economies - Lucia Mangiavacchi (IZA World of Labor, 2016)
Compared to developing economies, European transition economies had high levels of human capital when their transitions began, but a lack of resources and policies to protect poor families hampered children's access to education, especially for non-compulsory school grades. Different phenomena associated with transition also negatively affected children's education: e.g. parental absence due to migration, health problems, and alcohol abuse. These findings call for a greater policy focus on education and for monitoring of the schooling progress of children in special family circumstances.
Keywords: H52; I24; J12; J13; P36; 330; education; children; parental migration; parental health; civil wars